1986
DOI: 10.1111/j.1399-0039.1986.tb00478.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens and complement types in patients with intracranial saccular aneurysms

Abstract: The occurrence of HLA-A, -B, -C antigens and the HLA controlled complement factors (Bf, C2, C4) was investigated in an unselected group of 116 consecutively admitted patients with intracranial saccular aneurysms, and compared to that of healthy controls (blood donors). When multiplying the p-values with the number of comparisons made, none remained significant. However, a rather high etiologic fraction of the BfS gene (0.59) was obtained. Moreover, for HLA -B7 a significant deviation from the Hardy-Weinberg eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The genetic associations between HLA molecules and the pathogenesis of IAs have been widely debated in the last century ( Lye and Dyer, 1989 ; Lye et al, 1989 ), but little research has been conducted recently. Ostergaard et al (1986) found that HLA-DR2 antigen frequency is significantly increased (66.7% vs. 29.7%, p < 0.01) in IAs compared to healthy controls. However, a later study conducted by Schievink et al (1988) revealed no significant difference in the HLA-DR2 frequency between IAs and controls, which was further supported by the findings of Lye and Dyer (1989) .…”
Section: Discussionmentioning
confidence: 84%
“…The genetic associations between HLA molecules and the pathogenesis of IAs have been widely debated in the last century ( Lye and Dyer, 1989 ; Lye et al, 1989 ), but little research has been conducted recently. Ostergaard et al (1986) found that HLA-DR2 antigen frequency is significantly increased (66.7% vs. 29.7%, p < 0.01) in IAs compared to healthy controls. However, a later study conducted by Schievink et al (1988) revealed no significant difference in the HLA-DR2 frequency between IAs and controls, which was further supported by the findings of Lye and Dyer (1989) .…”
Section: Discussionmentioning
confidence: 84%
“…A significantly increased frequency of HLA antigen A28, a significantly decreased frequency of both HLA antigen B40 and complement factor C4B2 were found in the serum of IA patients when compared with controls (174). In other association studies, HLA DR2, and DR7 alleles were found to be associated with IA (175, 176).…”
Section: Association Studies Try To Confirm the Candidate Loci Of Iamentioning
confidence: 78%